Assessment Strategies for Promoting Critical Reflection in Graduate-Level Programs - Sheybani, Omid; Jalilvand, Nasrin (Assessment and Practice in Educational Sciences, 2024)
This study aimed to explore the assessment strategies employed by graduate-level instructors to promote critical reflection in academic programs. A qualitative research design was employed, using semistructured interviews to gather data from 19 university instructors in Tehran with experience teaching at the graduate level. Participants were purposively selected from a range of disciplines, ensuring variation in assessment practices and pedagogical approaches. Data collection continued until theoretical saturation was reached. All interviews were audio-recorded, transcribed verbatim, and analyzed using thematic analysis supported by NVivo software. Open coding was followed by axial and selective coding to identify major themes, subthemes, and emergent concepts. Three primary themes emerged from the analysis: (1) Reflective Assessment Design, including the use of journals, structured prompts, rubrics, multimodal formats, and iterative reflection cycles; (2) Instructor Facilitation Strategies, such as dialogic feedback, emotional safety, peer-based reflection, and scaffolding techniques; and (3) Institutional Support Mechanisms, involving flexible assessment policies, professional development, technological resources, and interdepartmental collaboration. Participants emphasized that critical reflection was best supported when assessment design was intentional, reflection was scaffolded over time, and institutional structures were responsive to innovative pedagogy. Cultural responsiveness and emotional safety were also found to be critical enablers of deep student reflection. The study highlights the multidimensional nature of reflective assessment and underscores the need for deliberate instructional design, faculty facilitation, and institutional alignment to support critical reflection in graduate education. Findings suggest that effective reflective practices are context-sensitive, requiring cultural awareness, iterative design, and sustained institutional support. The insights contribute to the global discourse on reflective pedagogy by offering evidence from a non-Western academic setting.